Interplay between Carbonate Phases in the NaNO3‑Promoted Carbonation of MgO - Elena Willinger (1660549) (2025)
The reversible carbonation of magnesium oxide represents a promising route for efficient CO2 capture and storage. The uptake capacity can be significantly enhanced by the presence of molten alkali nitrate and carbonate promoters such as NaNO3 and Na2CO3. Yet, the mechanistic role of these promoters in accelerating CO2 uptake remains insufficiently understood. Here, by combining electron microscopy with X-ray diffraction, we elucidate the sequence of carbonation reactions occurring at the interface between liquid NaNO3, gaseous CO2, and a single-crystalline MgO substrate. We identify Na2Mg(CO3)2 as a transient precursor phase that dominates the early stages of carbonation and persists as a key intermediate supplying growth species for the MgCO3 product. The phase evolution follows an interface-coupled dissolution–precipitation pathway within a thin interfacial NaNO3 layer, where local dissolution of Na2Mg(CO3)2 is directly coupled to the precipitation of MgCO3. These insights into the coupling of CO2 uptake, Mg2+/O2– dissolution, supersaturation in the molten promoter, and precipitation across different stability regimes advance the fundamental understanding of nonequilibrium phase dynamics in molten salt-promoted carbonation.